SURVEI MINAT BEROLAHRAGA MASYARAKAT KOTA LUBUKLINGGAU DI TAMAN OLAHRAGA SILAMPARI (TOS) PASCA PANDEMI COVID-19 - Syafutra, Wawan; Darsi, Helvi; Setiawan, Hera (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This study aims to find out the Interest in Exercising of the People of Lubuklinggau City at the Silampari Sports Park (TOS). The results of the analysis showed that the factors from within with the need indicator were 79.67% or in the good criteria, the experience indicator was 73.34% or in the good criteria, in the attention indicator there was a result of 73.34% or in the good criteria, the interest indicator was 80% or in the good criteria, and the comfort indicator was 80% or in the good category. Then external factors with the indicator of interest have a result of 80% or in the criterion of good, the indicator of comfort has a result of 80% or in the criterion of good, while the indicator of infrastructure facilities has a result of 83.34% or in the criterion of very good. Based on the results of the research, the overall results show that the interest in sports of the people of Lubulinggau city in the Silampari Sports Park (TOS) is mostly in the very high category, namely frequency 12 with a percentage of 40%, in the high category, namely frequency 9 with a percentage of 30%, in the medium category, namely frequency 4 with a percentage of 13.34%, in the very low category, namely frequency 5 with a percentage of 16.67%.